2020
DOI: 10.1155/2020/5439836
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of Economically Important Cattle Diseases Using Participatory Epidemiology Tools in Lalibela, Sekota, and Ziquala Districts of Amhara Region, Northern Ethiopia

Abstract: Ethiopia’s livestock resource is one of the largest globally. It is estimated at around 59.5 million cattle, about 30.5 million sheep, and 30.2 million goats. The sector is irreplaceable in the means of livelihood of the population as a source of meat, milk, drought power, and income. Yet, the country is unable to exploit the sector entirely because of highly prevalent infectious diseases and lack of appropriate disease control policy. These constraints are worse in districts of Lalibela, Sekota, and Ziquala, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In developing country particularly, Ethiopia is the home of huge numbers of livestock as well infectious and noninfectious diseases. Therefore, the veterinary vaccine is used primarily to promote animal health by preventing disease outbreaks that can have a devastating effect on animal production, as well as on human and animal health [6,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing country particularly, Ethiopia is the home of huge numbers of livestock as well infectious and noninfectious diseases. Therefore, the veterinary vaccine is used primarily to promote animal health by preventing disease outbreaks that can have a devastating effect on animal production, as well as on human and animal health [6,19].…”
Section: Discussionmentioning
confidence: 99%
“…Despite having this massive amount of resource, the Ethiopia is unable to exploit the sector entirely because of highly prevalent infectious diseases and lack of appropriate disease control policy [6]. Diseases have many negative impacts on the production and productivity of farm animals including imposing significant economic losses due to mortality, morbidity, loss of weight, poor growth rate, and poor fertility, and reduced animal draft power [7].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Indeed, in this study, there was a wide variation of disease list lengths (number of listed diseases) between countries whatever the prioritization method used. Prioritization processes were held during a workshop (or focus group discussion and surveys) following a preparation period lasting several months and deeply relying on local partners’ engagement and implication of technical and financial partners [ 3 , 10 , 35 , 36 ]. Criteria identification and/or weighing or disease classification based on previously identified criteria were performed by the selected participants.…”
Section: Discussionmentioning
confidence: 99%
“…Livestock keepers in Africa are rural poor pastoralists, and with regard to priority diseases, it has been found that the perception of the poor themselves varied widely from expert opinion and para-veterinarians and community animal health workers that share the day-to-day life of farmers [ 75 ]. Thus, at the local level despite not being diseases properly speaking, ectoparasite infestations were top ranked, followed by known diseases or syndromes such as contagious bovine pleuropneumonia (CBPP), foot and mouth disease (FMD), blackleg, bloody diarrhea, and pasteurellosis [ 35 ]. Similarly, at national/regional levels, the top constraints that emerged from a prioritization process including three approaches (literature review, expert workshops, and para-veterinarian practitioner surveys) were endo/ectoparasites, FMD, brucellosis, peste des petits ruminants, Newcastle disease, avian influenza, contagious caprine pleuropneumonia, contagious bovine pleuropneumonia, mastitis, reproductive disorders, and nutrition constraints [ 36 ].…”
Section: Discussionmentioning
confidence: 99%